Key changes in Mongolian higher education statistics (Studia Philosophiae Et Juris, 2025)
This article briefly describes the history of the development of higher education in the Mongolian People's Republic and Mongolia, and examines changes in graduates’s professions based on education statistics and historical documents. Results of the study show that during the socialist era the main professions and specialties of graduates were medicine, Mongolian language and literature, engineering, Russian language, mathematics, accounting and economics. In modern times, graduates in business, management, and law have taken over 1/3 of all graduates. Moreover, the ranking of art and humanities has elevated. On the contrary, physics has devalued and the high ranking of engineering, manufacturing, and construction has lowered. Prior to 1990, the higher educationsystem was aimed at health caring and educating the population, as well at training specialists and leaders of the socialist society to develop agriculture and industry in the country. Nowadays, business and management dominate in modern higher education.Монголын дээд боловсролын салбарын статистикХураангуй: Энд БНМАУ ба Монгол улсын дээд боловсролын хөгжлийн түүхийг товч өгүүлж, их, дээд сургууль төгсөгчдийн мэргэжлийн статистик болон холбогдох баримтыг харьцуулж шинжилсэн. Судалгааны дүнгээс үзвэл, социализмын үед хүний их эмч, монгол хэл, утга зохиол, инженер, орос хэл болон тоо физик, нябо, эдийн засагч гэсэн мэргэжлээр голлон төгсдөг байсан бол орчин үед бизнес, удирдахуй, хууль эрх зүйгээр төгсөгчид нийт төгсөгчдийн 1/3-ийг эзлэх болсон байна. Мөн инженер, үйлдвэрлэл, барилга угсралтын мэргэжлийн эрэмбэ ухарч, тоо физикийн мэргэжил урлаг хүмүүнлэгт түрэгджээ. 1990 оноос өмнө манай улсын дээд боловсролын систем нь хүн амыг эрүүлжүүлэх, гэгээрүүлэхийн зэрэгцээ социалист нийгмийн мэргэжилтэн, удирдагчид бэлтгэж, ХАА, үйлдвэрлэл хөгжүүлэх чиглэлтэй байсан бол өнөөгийн дээд боловсролд бизнес ба удирдахуй давамгайлж байна.Түлхүүр үгсМонгол улс, дээд боловсрол, социализм, төгсөгчид, мэргэжил